Synthesis of α-Fe2O3-functionalised graphene oxide nanocomposite by a facile low temperature method and study of its magnetic and hyperfine properties - Nag, Sanchayita; Roychowdhury, Anirban; Das, Dipankar; Mukherjee, Sampad (Materials research bulletin, 2016)
[Display omitted] •Synthesis of reduced graphene oxide (rGO)/α-Fe2O3 nanocomposites (NCs) by sol–gel method.•Samples exhibited ferromagnetism originated due to surface canted spins.•rGO enhanced the value of saturation magnetization and coercivity of the bare nanoparticle.•RKKY coupling between the isolated rGO spins and the magnetic nanoparticles. Reduced graphene oxide/α-Fe2O3 nanocomposites were synthesized by a simple sol–gel method. Initially, the samples were investigated by X-ray diffraction, high resolution transmission electron microscopy and Raman spectroscopy. High resolution transmission electron micrographs indicate that the magnetic nanoparticles are well dispersed in the reduced graphene oxide sheet-like structure. Fourier transform infrared spectroscopy studies corroborate the results obtained by X-ray diffraction. Temperature as well as field dependent magnetic measurements revealed ferromagnetism in the pristine α-Fe2O3 as well as in the nanocomposite sample that is attributed to surface canted spins and defects present in the samples. The enhanced value of coercivity in case of the nanocomposite sample could be ascribed to the Ruderman–Kittel–Kasuya–Yosida type of interaction between the isolated reduced graphene oxide spin and the magnetic ions. Presence of super paramagnetic doublet as well as sextet patterns related to hematite phase is confirmed by the 57Fe-Mössbauer spectroscopy.